Credit Union Regulatory Improvements Act of 2005 (CURIA). (U.S. Congressional Research., 2005)
Summarizes major provisions of the Credit Union Regulatory Improvements Act of 2005, to revise regulation of credit unions to alleviate regulatory burdens.